Development of the drive system for a four-phase switched reluctance motors - Rdtuad, Paiwan Ke; Ttiratsatcha, Supat Ki (My University, 2014)
This paper presents the development of the drive system for a four-phase Switched Reluctance Motor (SRM). The drive system are consists of the experimental and the software control scheme. The experimental system is designed for a four-phase 8/6 3Hp SRM. The control scheme are consists of the speed control and the two-quadrant control. The speed control scheme is used PI controller to calculate reference value of the phase current, the phase current can control in both soft chopping and hard chopping modes. The two-quadrant control scheme is used an analog switch to control the operation modes from motoring to generating (braking). The control schemes are implemented on the TMS320F2812 DSP which is a main controller. The SRM drive system that obtained from this research will be used in the future works. © 2014 IEEE.
Keywords: Asymmetrical Converter; Digital Signal Processing (DSP); Hard Chopping Mode; Single Pulse Mode; Soft Chopping Mode; Switched-Reluctance Motor (SRM)